HPV transcription in skin tumors - Hultin, Emilie (PLoS One, 2019)
BACKGROUND: Although more than 95% of viral sequences found in skin tumors typically belong to human papillomaviruses (HPVs), HPV transcription has so far not been detected. As current technology allows very deep transcriptome sequencing, we examined skin tumors and precursor lesions for HPV transcription. METHOD: Fresh frozen biopsies from 12 skin specimens (11/12 were positive for HPV DNA) were subjected to total RNA sequencing. The cervical cancer cell line CaSki was included as a positive control for HPV transcription. RESULTS: HPV RNA was detected and confirmed in 1/12 skin lesions at a median depth of 66 million reads per sample. One specimen was positive for HPV 110 transcripts mapping to E6, E7, E2/E4 and L2 open reading frames, as well as to a spliced E1^E4 transcript. CONCLUSION: In conclusion, the study revealed that a minority of skin lesions contains HPV transcripts and that HPV DNA detection does not predict HPV transcriptional activity.